Beyond UTSMMA and MMETROPLAN: Other Transport-Related Plans, Reports, and Position Papers, 1968–1982 - Daguio, Keith Gerard; Lagman, Marco Stefan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Starting in the 1960s, traffic congestion became a staple part of Manila’s history. Rapid urbanization, century-old thoroughfares, and large-scale migrations to Manila are just some of the reasons for the worsening traffic conditions. During the Marcos Era, the academe, practitioners, government agencies, and various organizations produced plans, position papers, and transport documents that sought to understand, assess, and perhaps provide possible solutions. Using data available in the libraries of University of the Philippines Diliman, this research note seeks to provide an initial survey and preliminary review of transport materials that documented and proposed solutions to the traffic congestion in the city of Manila from the 1960s until the 1980s.
Keywords: Manila; transport history; transport planning